Profitability and growth opportunity: Impact on company value - Whetyningtyas, Aprilia; Arumsari, Nurul Rizka; Ashari, Ashari; Mulyani, Sri (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This research aims to examine and analyze the impact of profitability and growth opportunity on company value in healthcare companies listed on the IDX in 2018-2022. Method: The sampling method used in this research was purposive sampling. The data analysis method employed in this research was multiple linear regression analysis. Results: The research results show that profitability has no effect on company value, while growth opportunity has a negative effect on company value. Conclusions: This study concludes that profitability does not significantly affect company value, whereas growth opportunities negatively impact it. Limitations: This study has limitations, notably the low determination coefficient of 17.6%.    Contribution: The contribution of this research to companies in the healthcare sector is to provide insight into the importance of profitability and growth opportunities in increasing company value. Novelty: The novelty of this research compared to previous studies lies in three aspects: First, the inclusion of growth opportunity as an independent variable. Second, the use of the PBV indicator for measuring company value, as opposed to the Tobin's Q indicator used in prior studies. Third, the focus of this research is on the healthcare sector, in contrast to previous studies that focused on the food and beverage industry.